The effect of the beta(2) adrenoceptor gene Thr164Ile polymorphism on human adipose tissue lipolytic function - Hoffstedt, Johan (2001)
1. A rare β(2)-adrenoceptor gene polymorphism, Thr164Ile, has been described that impairs receptor function when transfected into cell lines. We investigated whether the polymorphism influences native receptor function by studying lipolysis in freshly isolated subcutaneous fat cells from 236 apparently healthy subjects. 2. Twelve subjects were heterozygous for the 164Ile variant. The fat cells of Ile carriers displayed a 6 fold increase (P=0.02) in the lipolytic EC(50) of terbutaline (a selective β(2)-adrenoceptor agonist), but no change in the lipolytic action of dobutamine (a selective β(1)-adrenoceptor agonist), compared with the Thr carriers. Maximum adrenoceptor agonist stimulated lipolysis did not differ between Thr and Ile carriers. 3. The influence of two other polymorphisms (Arg16Gly and Gln27Glu) in the β(2)-adrenoceptor gene was considered. Six 164Ile carriers also carried the 16Gly and 27Glu alleles. The latter combination occurred among 105 of the 164Thr carriers. For the 16Gly27Glu subgroup, the EC(50) of terbutaline was about 10 fold higher in 164Ile as than in 164Thr carriers (P=0.02) but there was no difference between genotypes in maximum terbutaline action. There was no difference between groups in dobutamine action. 4. In conclusion, the 164Ile variant of the β(2)-adrenoceptor is associated with a decreased native adipocyte receptor function, as evidenced by a marked increase in the half maximal effective concentration of the lipolytic action of a selective β(2)-adrenoceptor agonist. This suggests that genetic variance in the β(2)-adrenoceptor gene might be important for catecholamine function in humans, at least as far as adipocyte lipolysis is concerned.